1997
DOI: 10.1152/ajpheart.1997.272.3.h1165
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytosolic Ca2+ and protein kinase C in developing myogenic contraction in isolated rat small arteries

Abstract: Cytosolic Ca2+ and protein kinase C (PKC) may regulate the myogenic contraction of arterial myocytes. The role of these second messengers is examined in skeletal muscle small arteries, which have strong myogenic activity, and mesenteric small arteries, which have weak myogenic activity. The vessels were isolated and cannulated. The inner diameter was measured with a video-digitizing system. Cytosolic Ca2+ concentration was assessed by fura 2. Skeletal muscle small arteries dilated from 122 +/- 6 to 153 +/- 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…The mechanistic basis of the myogenic response is calciumdependent activation of the actin-myosin motor unit, as evidenced by a brisk rise in VSM intra-cellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in response to the mechanostimulus of pressure and by subsequent phosphorylation of myosin light chain kinase (3,22,34). However, other factors also play a role in the initiation and maintenance of myogenic vasoconstriction, reviewed most recently by Davis and Hill (5); of these, that which has direct bearing on the present work is PKC (6,13,15,16,19,27). For example, pressure stimulation applied to coronary arterioles caused a transient increase in [Ca 2ϩ ] i , but a sustained translocation of PKC␣ from cytosol-to-membrane in VSM, indicating its activation (6).…”
mentioning
confidence: 80%
“…The mechanistic basis of the myogenic response is calciumdependent activation of the actin-myosin motor unit, as evidenced by a brisk rise in VSM intra-cellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in response to the mechanostimulus of pressure and by subsequent phosphorylation of myosin light chain kinase (3,22,34). However, other factors also play a role in the initiation and maintenance of myogenic vasoconstriction, reviewed most recently by Davis and Hill (5); of these, that which has direct bearing on the present work is PKC (6,13,15,16,19,27). For example, pressure stimulation applied to coronary arterioles caused a transient increase in [Ca 2ϩ ] i , but a sustained translocation of PKC␣ from cytosol-to-membrane in VSM, indicating its activation (6).…”
mentioning
confidence: 80%
“…170 Evidence is accumulating that L-type voltagegated calcium channels and protein kinase C determine myogenic tone under physiological conditions. 171 Korzick et al 172 demonstrated that increased myogenic tone in trained pigs involves changes in protein kinase C-␣ expression and phosphorylation, which augment the depolarization-related opening of voltage-gated calcium channels in smooth muscle cells and increase of intracellular calcium.…”
Section: Myogenic Controlmentioning
confidence: 99%
“…The arterial pressure in one leg was maintained reduced for 3 mo by ligation of the external iliac artery, and the contralateral artery served as a control. With the use of a pressure myograph, we studied the correlation between structure and myogenic responsiveness in these arteries with different structure but from the same genetic and humoral environment.The cellular mechanisms of the myogenic response include depolarization and subsequent opening of voltage-operated calcium channels (16,23,24,34), but nonelectromechanical coupling mechanisms also appear to be involved (1,26). It has been shown that pressure-induced activation enhances the calcium sensitivity of the contractile machinery (33).…”
mentioning
confidence: 99%
“…The cellular mechanisms of the myogenic response include depolarization and subsequent opening of voltage-operated calcium channels (16,23,24,34), but nonelectromechanical coupling mechanisms also appear to be involved (1,26). It has been shown that pressure-induced activation enhances the calcium sensitivity of the contractile machinery (33).…”
mentioning
confidence: 99%